OPTIMIZING PROFITABILITY: A DEEP DIVE INTO CASH AND RECEIVABLE TURNOVER WITH WORKING CAPITAL TURNOVER AS THE MODERATOR - Neng Asiah; Dian Sulistyorini Wulandari; Sabbarudin (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze the effect of asset turnover and receivable turnover on profitability with working capital turnover as a moderating variable. The object of the research is manufacturing companies listed on the Indonesia Stock Exchange during the period 2019–2023. A quantitative approach using panel data regression analysis was employed. The results indicate that both asset turnover and receivable turnover have a positive and significant impact on profitability. Furthermore, working capital turnover significantly moderates the relationship between these operational efficiency metrics and profitability. This implies that firms with higher working capital efficiency can enhance the positive effect of asset and receivable utilization on financial performance. The study contributes to financial management by emphasizing the need for integrated strategies that combine operational efficiency with effective working capital management to improve profitability.